Effect of Brand Image, Consumer Attitude, and Price Perception with e-WOM as Mediator towards Customer Purchase Intention of Customized Resin Products - Ulwi Bertha Pratiwi Putri; Metta Padmalia (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study examines the influence of brand image, consumer attitude, and price perception on purchase intention, with e-WOM as a mediator in the customized resin product sector. Methodology: Using SmartPLS4 was conducted on 220 respondents interested in purchasing Glow Resin Art products through the Shopee platform. Results: The results indicate that brand image (β = 0.214, p = 0.001), consumer attitude (β = 0.169, p = 0.004), and price perception (β = 0.176, p = 0.006) have positive and significant effects on customer purchase intention. Furthermore, e-WOM significantly mediates the relationships between brand image, consumer attitude, and price perception on purchase intention, as evidenced by all T-statistics exceeding 1.960 and p-values below 0.05. Findings: Positive marketing factors ignite enthusiastic e-WOM, which significantly elevates customer purchase intention. Novelty: This study innovatively examines e-WOM as a crucial mediator between marketing factors and purchase intention. Originality: e-WOM strengthens consumer perceptions and enhances purchase intention. Conclusion: Brand image, consumer attitude, and price perception significantly boost customer purchase intention, both directly and through e-WOM as a mediating factor in the customized resin market. Type of Paper: Quantitative empirical.